An investigation into the development of the absorptive capacity of manufacturing SMEs. Issue 23 (2nd December 2017) - Saad, Mohammed; Kumar, Vikas; Bradford, John
Abstract : To sustain their competitive advantage in a highly competitive landscape, SMEs, in spite of their limited resources, need to effectively learn. The ability to access and successfully use knowledge is at the heart of absorptive capacity. The main purpose of this empirical study is to investigate the importance of awareness as an antecedent dimension of the concept of absorptive capacity of manufacturing SMEs from aerospace and advanced engineering industry in the UK. The study will also attempt to explore the impact of awareness on the other dimensions of absorptive capacity. Awareness is related to the importance, motivation and interest of learning and innovating. Our study, which focuses on internal processes adopts a mixed method approach and is based on the data collected from 43 SMEs. Our finding suggests that awareness as an antecedent dimension can play a vital role in helping SMEs to improve their knowledge-based resources through changes within their internal organisational and cognitive processes.